PENGARUH CURRENT RATIO, DEBT TO EQUITY RATIO DAN TOTAL ASSET TURNOVER TERHADAP RETURN ON ASSET (STUDI PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2020) - Ayu Wulandari, Bella; Agus Santoso, Rahmad (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2023)
This study aims to determine whether the Current Ratio, Debt to Equity Ratio and Total Asset Turnover have a significant effect to Return On Asset in banking companies listed on the Indonesia Stock Exchange in 2018-2020. The population used in this study were all banking companies listed on the Indonesia Stock Exchange in 2018-2020 which amounted to 16 companies was observed for 3 years, starting from 2018 to 2020. The test is carried out using multiple regression. The result show that the Current Ratio does not have significant effect on Return On Asset, the Debt to Eequity Ratio has a a significant effect on Return On Asset, and Total Asset Turnover has a significant effect on Return On Asset.